The role of storytelling in the conservation of cultural heritage: The case of Santa Lucía, Guayas - Ruíz Murillo, Jorge Rodrigo (2025)
This paper examines the role of storytelling in preserving cultural heritage, with a focus on the case of Santa Lucía, Guayas. In a context where cultural traditions face challenges such as migration, a lack of interest among younger generations, and globalisation, the primary objective of the study was to analyse storytelling as a tool for safeguarding cultural heritage in the canton of Santa Lucía. The research employs a qualitative approach, including interviews with community members, particularly elders, as well as experts in cultural heritage and marketing, complemented by direct observation of local cultural practices. The main findings highlight storytelling as a powerful means of connecting generations, transmitting values, and fostering community engagement. Storytelling enhances the sense of belonging and serves as a vehicle for heritage education, raising awareness among both youth and adults. The study concludes that storytelling not only preserves cultural heritage but also revitalises it. Moreover, digital technology amplifies its reach, while community participation ensures that traditions remain alive and relevant in the face of contemporary challenges.